Lupine triterpenoids from the Rubus corchorifolius and their chemotaxonomic significance. (February 2022) - Zhang, Yu; Dai, De-Cai
Abstract: The phytochemical investigation of the stems of Rubus corchorifolius L. f. led to the isolation of a new lupine triterpenoid, rubuslupine (1 ), together with seven known biogenetically related lupine triterpenoids (2 –8 ). The structures of these compounds were elucidated using comprehensive spectroscopic methods. Compounds 1–4 and 6–8 were isolated from the R. corchorifolius for the first time. The chemotaxonomic significance of the isolates was also discussed. Graphical abstract: Image 1 Highlights: A new lupine triterpenoid, rubuslupine (1 ) was isolated. Seven lupine triterpenoids were isolated for the first time from the Rubus corchorifolius. The lupine triterpenoids may have a role as chemotaxonomic markers for Rubus corchorifolius.